Effect of Lead stress on phosphatase activity and reducing power assay of Triticum aestivum - Gubrelay, U; Agnihotri, R K; Shrotriya, S; Sharma, R (Cellular and Molecular Biology, 2015)
Lead (Pb) is a highly toxic heavy metal for both plants and animals; the environment is increasingly polluted with heavy metals and reduces crop productivity. Plants possess homeostatic mechanisms that allow them to keep correct concentrations of essential metal ions in cellular compartments and to minimize the damaging effects of an excess of nonessential ones. One of their adverse effects on plants are the generation of harmful active oxygen species, leading to oxidative stress and the antioxidative activity seems to be of fundamental importance for adaptive response of plant against environmental stress. The present study explores the effects of lead (soil treated twice/ week) with (10, 30 and 60 mM) on the specific activities of phosphatases which might lead to reducing power assay in (Triticum aestivum PBW344) seedling. A significant decrease in the redox potential of shoot compared to root was observed at the similar concentration of lead. A similar trend on leaves was also noted. Acid and alkaline phosphatase activities were significantly higher in roots than in shoot at all the three concentration of lead i.e. 10, 30 and 60 mM, compared to controls. The above mentioned changes were more pronounced at 60 mM concentration of lead than two other concentrations. These results lead us to suggest that increased lead concentration in soil might lead to adverse effects on plant growth and phosphatase activities.